2023
DOI: 10.1126/sciadv.ade0423
|View full text |Cite
|
Sign up to set email alerts
|

Flexible biomimetic block copolymer composite for temperature and long-wave infrared sensing

Abstract: Biological compounds often provide clues to advance material designs. Replicating their molecular structure and functional motifs in artificial materials offers a blueprint for unprecedented functionalities. Here, we report a flexible biomimetic thermal sensing (BTS) polymer that is designed to emulate the ion transport dynamics of a plant cell wall component, pectin. Using a simple yet versatile synthetic procedure, we engineer the physicochemical properties of the polymer by inserting elastic fragments in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Unfortunately, the low solubility of the bismuth precursors prevented control of the doping degree. Besides, it has been reported that ionic compensation of point defects could impact doping efficiency. , On the other hand, the 40 mV K –1 thermal voltage produced by MABiI and S.MABiI can be exploited in thermoelectronics. , Bi-based perovskite derivates are also easily processable, scalable, and cost-effective, and if MABiI and S.MABiI were employed in thermoelectronics, they could allow the device to scale down from millimeters to microns and deliver a thermal voltage higher than that reported in conventional devices. Besides, low-dimensional perovskite derivates are increasingly attracting the interest of applied research, thanks to the possibility of exploiting the phenomena resulting from charge confinement in bulk materials.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the low solubility of the bismuth precursors prevented control of the doping degree. Besides, it has been reported that ionic compensation of point defects could impact doping efficiency. , On the other hand, the 40 mV K –1 thermal voltage produced by MABiI and S.MABiI can be exploited in thermoelectronics. , Bi-based perovskite derivates are also easily processable, scalable, and cost-effective, and if MABiI and S.MABiI were employed in thermoelectronics, they could allow the device to scale down from millimeters to microns and deliver a thermal voltage higher than that reported in conventional devices. Besides, low-dimensional perovskite derivates are increasingly attracting the interest of applied research, thanks to the possibility of exploiting the phenomena resulting from charge confinement in bulk materials.…”
Section: Results and Discussionmentioning
confidence: 99%
“… 49 , 56 59 Bi-based perovskite derivates are also easily processable, scalable, and cost-effective, and if MABiI and S.MABiI were employed in thermoelectronics, they could allow the device to scale down from millimeters to microns and deliver a thermal voltage higher than that reported in conventional devices. 59 68 Besides, low-dimensional perovskite derivates are increasingly attracting the interest of applied research, thanks to the possibility of exploiting the phenomena resulting from charge confinement in bulk materials.…”
Section: Results and Discussionmentioning
confidence: 99%
“…For instance, the composite based on a polymer matrix and electrically conductive fillers is a pioneering scheme which utilizes the contact resistance variation caused by thermal-induced volume expansion, achieving high TCR and a temperature sensitivity of 20 mK . Pectin and biomimetic pectin have also shown promise, with temperature sensitivity exceeding 10 mK, which represents the highest temperature sensitivity among current state-of-the-art flexible resistive temperature sensors. , However, there is still a lack of predictive models to guide the further development of flexible temperature sensors, particularly in achieving a thermal sensitivity of 1 mK or higher.…”
mentioning
confidence: 99%
“…18 Pectin and biomimetic pectin have also shown promise, with temperature sensitivity exceeding 10 mK, which represents the highest temperature sensitivity among current state-of-the-art flexible resistive temperature sensors. 19,20 However, there is still a lack of predictive models to guide the further development of flexible temperature sensors, particularly in achieving a thermal sensitivity of 1 mK or higher.…”
mentioning
confidence: 99%